2021
DOI: 10.1080/02602938.2021.1968791
|View full text |Cite
|
Sign up to set email alerts
|

Developing digital creativity through authentic assessment

Abstract: Digital creativity, the use of digital tools and technologies to explore creative ideas and new ways of displaying your ideas, research or work, is emerging as an important competency for graduates across many disciplines. The development of digital creativity competency in domains traditionally perceived as being less creative, including the accounting profession, has yet to be explored. This study reports on the use of an authentic assessment for learning to develop students' digital creativity in an undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…One study found that despite the rapid growth of digitalization, organizations lack strategies to creatively use digital technology, which is called the “digital impasse.” The main reason for this dilemma is the lack of digital creativity ( Shao et al, 2021 ). Digital creativity is becoming a very important competency ( Van Rensburg et al, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…One study found that despite the rapid growth of digitalization, organizations lack strategies to creatively use digital technology, which is called the “digital impasse.” The main reason for this dilemma is the lack of digital creativity ( Shao et al, 2021 ). Digital creativity is becoming a very important competency ( Van Rensburg et al, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…With the rapid development of digital technologies such as big data, artificial intelligence, cloud computing, and the blockchain, the world has entered the digital era of rapid change and innovation ( Yoo et al, 2010 ; Grover et al, 2020 ). Organizations and individuals are undergoing significant transformation as a result of digitization ( Van Rensburg et al, 2021 ). Therefore, it is very important to adapt to digital trends and enhance digital ability ( Shao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations